DEFICIT IRRIGATION EFFECTS ON SOIL NUTRIENT DYNAMICS AND YIELD PERFORMANCE OF MAIZE (ZEA MAYS L.) - Chike Pius Nwachukwu; Chukwuemeka Obumneme Umobi; Luke Okwuchukwu Uzoigwe (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2025)
A field experiment was conducted at the Experimental Farm/Workshop of the Department of Agricultural and Bioresources Engineering, Nnamdi Azikiwe University, Awka, Nigeria, to evaluate the effects of deficit irrigation on soil chemical properties, yield, and yield components of maize. The study was laid out in a randomized complete block design with three replications and six irrigation regimes based on crop evapotranspiration (ETc), namely 100% ETc (full irrigation), 80% ETc, 60% ETc, 50% ETc, 40% ETc, and 30% ETc. Measured parameters included maize yield, 1000-grain weight, cob weight, soil electrical conductivity (EC), nitrogen, phosphorus, potassium, and soil pH. Maize yield ranged from 1,420 to 2,580 kg/ha, while 1000-grain weight varied between 162 and 342 g. Cob weight ranged from 352 to 398 g. Soil EC varied between 50.8 and 55.6 µS/cm, nitrogen ranged from 1.08 to 1.86 g/kg, phosphorus ranged from 3.10 to 7.72 mg/kg, potassium ranged from 6.5 to 9.2 ppm, and soil pH ranged from 6.08 to 7.02. Analysis of variance showed significant (p < 0.05) effects of irrigation treatments on yield and most soil chemical properties. Moderate deficit irrigation improved water use efficiency and maintained soil fertility within optimal ranges, moderate deficit irrigation is a viable and sustainable strategy for maize production in Awka, as it reduces water use while maintaining high yield and improving nutrient retention.